Mengukur Persepsi Peserta Didik tentang Lingkungan Belajar Konstruktivis Dihubungkan dengan Keterampilan Berpikir Kritisnya Pada Konsep Asam Basa - Tiara Bora; Lukman Abdul Rauf Laliyo; Mangara Sihaloho (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to measure students' perceptions of the constructivism learning environment and its relationship with critical thinking skills on the concept of Acid-Base, as well as assess the quality of critical thinking skills test items using the Rasch Model approach. The research was carried out in high school/MA/equivalent in the Gorontalo Regency area with a total of 549 respondents in grade XII. Data collection was used the Learning Environment Perception Questionnaire (CLES) and the Critical Thinking Skills Test (Facione). The results of the Rasch Model analysis showed that the instrument had excellent quality and was declared valid and reliable. The students' perception of the constructivist learning environment as a whole was in the positive category with a logite average value of +0.15. However, students' critical thinking skills were still in the low category with a logite average value of -1.04. Based on the Spearman's rho correlation test, it was found that a correlation coefficient of 0.519 with a significance value of p < .001. This shows that there is a real relationship between the perception of the constructivistic learning environment and the critical thinking skills of students. The higher the perception of students of the constructivist learning environment, the higher their critical thinking skills in acid-base material.